Calidad de Servicio al Cliente y su incidencia en la Rentabilidad de las empresas del rubro Restaurantes – Pollerías del distrito de Tarapoto. Año 2014 - Meléndez Castillejos, Julio César (2014)
This study "Quality Customer Service and impact on profitability of companies in the category Restaurants - pollerías district of Tarapoto. 2014 "; aims to assess the quality management and customer service as impact on profitability in the said company, to know the level of quality management, customer service and customer perception towards the company; thus counting on 5 dimensions: responsiveness, reliability, security, tangibles and empathy important research which allowed and / or helped the description of the problems. In researching the questionnaire adapted to Servqual method was used to find the perceived quality of care for clients restaurants - pollerías Tarapoto district and interview the Manager and / or Manager of the company for information about your income and expenses averages to obtain an average yield of establishments. Assessment of quality management customer service shows that quality is important for companies that sell services and otherwise provide quality service that could directly affect the profitability of the company.